The controversy of sports technology: a systematic review - Dyer, B. (SpringerPlus, 2015)
Changes or introductions of technology or equipment can affect how a sport is played or influence its performances. This article conducted a systematic review of peer-reviewed literature to identify any case studies of controversial events surrounding the implementation or use of sports technology. 56 articles were identified that highlighted 31 different case studies found over a three decade time period. Thematic analysis revealed six distinctive themes when reviewing the articles. Whilst the sport of golf had the highest number of case studies, it was found that a significant level of attention had been recorded in the cases of Oscar Pistorius use of prosthetic legs in athletics and the use of full length swimsuits in swimming. The trend surrounding the number of articles was shown to be initially intermittent but saw a peak period from 2008 to 2010. However, the frequency of such articles since this peak has been more consistent. It is proposed that long periods of time without intervention or resolution by a governing body often increases the peer-reviewed attention paid to such cases in examples such as those identified in this systematic review.